PROBLEMS OF IMLA FOR ARABIC LITERATURE STUDENTS AT INDONESIAN MUSLIM UNIVERSITY (STUDY OF WRITING AND PART OF ARABIC TEXTS) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research focused on the problems of writing imla for students of Arabic literature at Indonesian Muslim University. The purpose of this study was to find out the causes of errors in writing imla for students of Arabic literature at Indonesian Muslim University and the problems that were faced by students of Arabic literature at Indonesian Muslim University. The population used in this study was all students of Arabic literature. The sample was 4th semester students. This research was a qualitative descriptive study, using data collection techniques through observation, interviews, questionnaires and documentation. The conclusion of this study was that there were errors in writing imla for students of Arabic literature, namely linguistic problems and non-linguistic problems. Linguistic problems consist of: 1. the difference between Arabic and Latin script. 2. Lack of understanding of Arabic vocabulary mastery. The problems faced by students in writing imla were: 1. Difficulties in writing when the lecturer read a sentence and some of the students had not been able to write it and had to distinguish one letter from another. 2. Difficulty in determining whether the writing was right or wrong because it still applied an online learning system. 3. Sometimes students are fooled by the short length of writing. 4. Difficulties in neatness and beauty of writing.